2015
DOI: 10.1016/j.nicl.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

[ 18 F]-fluoro- l -thymidine PET and advanced MRI for preoperative grading of gliomas

Abstract: PurposeConventional MRI based on contrast enhancement is often not sufficient in differentiating grade II from grade III and grade III from grade IV diffuse gliomas. We assessed advanced MRI, MR spectroscopy and [18F]-fluoro-l-thymidine ([18F]-FLT) PET as tools to overcome these limitations.MethodsIn this prospective study, thirty-nine patients with diffuse gliomas of grades II, III or IV underwent conventional MRI, perfusion, diffusion, proton MR spectroscopy (1H-MRS) and [18F]-FLT-PET imaging before surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 33 publications
0
42
0
3
Order By: Relevance
“…Then a 3-dimensional T1-weighted sequence was used to evaluate gadolinium enhancement (T1Gd sequence) as a reflection of vessel permeability. The cerebral blood volume (CBV) maps were computed with ImageJ software (National Institutes of Health, 2013), according to the method published by Collet et al (20).…”
Section: Mri Examinationmentioning
confidence: 99%
“…Then a 3-dimensional T1-weighted sequence was used to evaluate gadolinium enhancement (T1Gd sequence) as a reflection of vessel permeability. The cerebral blood volume (CBV) maps were computed with ImageJ software (National Institutes of Health, 2013), according to the method published by Collet et al (20).…”
Section: Mri Examinationmentioning
confidence: 99%
“…trapping is a representation of thymidine incorporation into DNA [11,12]. FLT-PET has been found useful for noninvasive grading and assessment of proliferative activity especially in newly diagnosed gliomas [13,14,15]. Moreover, FLT-PET can provide valuable information regarding treatment response and patient prognosis and regarding the recognition of tumour recurrence in gliomas [25,26].…”
Section: Based On the 2016 Who Classification Met-pet Studies In Patmentioning
confidence: 99%
“…This number means that one in 4 gliomas with low FLT uptake below the cutoff value (T/N ratio of 6.74) was an IHD1-wildtype tumour that could harbour an aggressive nature in the tumour. Our previous study showed that FLT uptake in tumours without an observed contrast enhancement effect on MR images was low even if the tumours were high-grade gliomas [15]. Later studies, including from our laboratory, have shown that the major portion of FLT uptake is due to increased transport and influx through the disrupted blood-brain barrier (BBB) [16,17].…”
Section: Based On the 2016 Who Classification Met-pet Studies In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Anreicherung des Proliferationsmarkers [ 18 F]-3′-deoxy-3′fluo rothymidin (FLT) korreliert mit dem Malignitätsgrad und Prognose von Hirntumoren [10], jedoch reichert sich FLT nur in Tumorregionen mit defekter BHS an und ist nicht geeignet, die Ausdehnung von zerebralen Gliomen korrekt wiederzugeben [29,57]. Des Weiteren wurden die Phospholipid-Vorläufer 11 C-Choline und 18 F-Fluorcholine als Marker des Zellmembranenumsatzes in Hirntumoren eingesetzt [25].…”
Section: Weitere Radiopharmaka Für Petunclassified